(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Transfusion of blood and blood components, as a specialized modality of patient management, saves millions of lives worldwide each year and reduces morbidity. Transmission of infectious diseases through donated blood is of concern in order to provide safe blood for transfusion which forms an integral part of medical and surgical therapy. The aim of the present study was to analyze the status of transfusion-transmitted infections among the apparently healthy donors to increase awareness of complications of blood transfusion and make the clinicians more vigilant with regard to judicious use of blood. Materials and methods: This retrospective study was carried out in the Department of Transfusion Medicine at Chattagram Maa-O-Shishu Hospital Medical College from January to December 2022. After proper ethical consideration, a total of 7,289 blood donors were included in this study. All the samples were screened for Hepatitis B surface antigen (HBsAg) Hepatitis C Virus (HCV) Human Immunodeficiency Virus (HIV) 1 and 2, Venereal Disease Research Laboratory test (VDRL) and malaria to determine the prevalence of TTI. All the healthy blood donors were 18 to 60 years old. Results: The prevalence of Hepatitis B Virus (HBV) HCV and syphilis was 3.014% and 0.109%, respectively. No blood donor tested positive for malarial parasites or HIV. Strictly maintain the donor selection criteria and mandatory screening of the donor’s blood for HBV, HCV, HIV, malaria and syphilis using sensitive laboratory screening tests to reduce the incidence of TTI in the Bangladeshi population and to ensure the safety of the blood for the recipient. Conclusion: Strictly maintain the donor selection criteria and mandatory screening of the donor’s blood for HBV, HCV, HIV, malaria and syphilis using sensitive laboratory screening tests to reduce the incidence of TTI in the Bangladeshi population and to ensure the safety of the blood for the recipient. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 49-52